If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -31 = x + 5 Reorder the terms: -31 + 5x = x + 5 Reorder the terms: -31 + 5x = 5 + x Solving -31 + 5x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -31 + 5x + -1x = 5 + x + -1x Combine like terms: 5x + -1x = 4x -31 + 4x = 5 + x + -1x Combine like terms: x + -1x = 0 -31 + 4x = 5 + 0 -31 + 4x = 5 Add '31' to each side of the equation. -31 + 31 + 4x = 5 + 31 Combine like terms: -31 + 31 = 0 0 + 4x = 5 + 31 4x = 5 + 31 Combine like terms: 5 + 31 = 36 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 9x+27x^2= | | -12n+16n+-19=-13 | | -3a+8b+61=0 | | 27.00/2.25 | | 1/38=5.5/x | | 2(c-8)+-6=8 | | -2x+3(x-3)=-13 | | 11=-5x+21 | | a^4+8=11 | | 6-7x=5x-10x+8 | | 3x+4=-39 | | 10=2(c+1)+2 | | 7(3x-2)=5(2x-1) | | 24x-3(8x-18)=54 | | 6x+2(2x-3)=24 | | 7p-6p=-11 | | Y=0.25x^2+10x+80 | | 3x^(-1/2)=8 | | 12-v=9 | | 4x+5x-34=68-8x | | 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 | | 7-z=-3 | | 12x+24y=60 | | ((4y^4/3x^4y^7))^3 |